The N‐terminal p.(Ser38Cys) TIMP3 mutation underlying Sorsby fundus dystrophy is a founder mutation disrupting an intramolecular disulfide bond. Issue 5 (6th February 2019) - Naessens, Sarah; De Zaeytijd, Julie; Syx, Delfien; Vandenbroucke, Roosmarijn E.; Smeets, Frédéric; Van Cauwenbergh, Caroline; Leroy, Bart P.; Peelman, Frank; Coppieters, Frauke
Abstract: Sorsby fundus dystrophy (SFD) is a macular degeneration caused by mutations in TIMP3, the majority of which introduce a novel cysteine. However, the exact molecular mechanisms underlying SFD remain unknown. We aimed to provide novel insights into the functional consequences of a distinct N‐terminal mutation. Haplotype reconstruction in three SFD families revealed that the identified c.113C>G, p.(Ser38Cys) mutation is a founder in Belgian and northern French families with a late‐onset SFD phenotype. Functional consequences of the p.(Ser38Cys) mutation were investigated by high‐resolution Western blot analysis of wild type and mutant TIMP3 using patient fibroblasts and in vitro generated proteins, and by molecular modeling of TIMP3 and its interaction partners. We could not confirm a previous hypothesis on dimerization of mutant TIMP3 proteins. However, we identified aberrant intramolecular disulfide bonding. Our data provide evidence for disruption of the established Cys36‐Cys143 disulfide bond and formation of a novel Cys36‐Cys38 bond, possibly associated with increased glycosylation of the protein. In conclusion, we propose a novel pathogenetic mechanism underlying the p.(Ser38Cys) TIMP3 founder mutation involving intramolecular disulfide bonding. These results provide new insights into the pathogenesis of SFD and other retinopathies linked to mutations in TIMP3, such as age‐related macular degeneration. Abstract : Sorsby fundus dystrophy (SFD) is a macular degeneration caused by mutations in TIMP3, the majority of which introduce a novel cysteine. Most studies hypothesize that mutant TIMP3 proteins with unpaired cysteines form abnormal disulfide‐bonded dimers. As opposed to this, we propose a novel pathogenetic mechanism for the N‐terminal p.(Ser38Cys) mutation, identified in three families with late‐onset SFD, comprising the formation of a novel intramolecular disulfide bond with a potential effect on TIMP3 glycosylation.